Legal Validity Of Ai Evidence In Criminal Cases Within Shariah Court Of Malaysia - ‘Aini Nur’aqilah Zabidi; Zizi Azlinda Mohd Yusof (USIM Press, 2024)
The use of Artificial Intelligence (AI) technology, including AI algorithms and digital evidence such as CCTV footage, has become increasingly prevalent in legal proceedings. This trend raises questions about the validity and admissibility of AI-generated evidence in Shariah court proceedings. While specific guidelines exist for the use of evidence in Shariah courts, the application of AI technology in this context requires careful scrutiny to ensure justice for all parties involved. This study aims to examine the legal validity and admissibility of AI-generated evidence within the framework of the Shariah Court Evidence Enactment of Malaysia. The research employs a qualitative methodology, primarily involving a comprehensive literature review of relevant scholarly articles. Additionally, semi-structured interviews with experts in AI and Islamic law are conducted to gather insights on the legal validity of AI evidence in Shariah criminal proceedings. Findings suggest a potential connection between AI-generated evidence and the types of digital documents and evidence already recognized in the Shariah court enactment. This connection may provide a basis for considering the validity and admissibility of AI-generated evidence in Shariah courts. The research aims to contribute to the alignment of legal proceedings with the principles of fairness and transparency inherent in Islamic jurisprudence. By addressing the challenges and opportunities presented by AI technology in Shariah courts, this study seeks to reinforce public trust in the legal system while ensuring adherence to Islamic legal principles.